The impact of using mobile applications to learn Arabic vo-cabulary among non-native secondary students: The impact of using mobile applications to learn Arabic vo-cabulary among non-native secondary students - Elsayed Ahmed, Ahmed Abdelkarim; Wan Ahmad, Wan Rusli; Mohamed Abdelmotaal, Manal; Osman Mukhtar Ahmed, Iman (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
Abstract This paper investigates the challenges faced by non-native secondary students to learn Arabic vocabulary as well as the preferred methods they prefer to use in learning Arabic vocabulary. A sample of 86 non-native students from Baseerah international school from grade 7 to grade 9 participated in this study. The sample answered a questionnaire that contains three sections, the first section is about the participants’ demographic data, the second section investigates the preferred learning style for Arabic vocabulary, and the third and last section investigates the preferred application content for learning Arabic vocabulary. The result of the study was clearly shown that students consider that one of the challenges is using the traditional way in learning Arabic vocab, on other hand they preferred to learn through using mobile Apps, the findings also shown that they believe that learning through mobile apps that include videos, pictures, and sound can help them to learn the Arabic vocabulary easier than the classic learning method. Besides, they can use games and fun tasks for revising the vocabulary which motivates them to learn and helps them to overcome the exams stress and feel confidence with their capabilities.